The discursive uses of aunque in Peninsular Spanish - Parra Araujo , Beatriz Goaveia Garcia; Gasparini Bastos, Sandra Denise (Entrepalavras, 2025)
Although it is traditionally presented as a concessive connective that links clauses in a relationship of counterexpectation, a survey of real data reveals that aunque can function as a discourse marker, linking larger textual units than the clause. Therefore, this study aims to describe the discursive uses of aunque in spoken and written Peninsular Spanish data. To do so, it adopts the theoretical model of Functional Discourse Grammar (FDG), whose architecture, organized into levels and hierarchical layers, considers pragmatics as the most comprehensive component, from which semantics, morphosyntax, and phonology are described. In addition to the theoretical framework of GDF, the concepts of Textual Linguistics presented in Jubran (2006a, 2006b) regarding the notion of discourse topic are also taken into consideration. The data collection involves sociolinguistic interviews extracted from the PRESEEA Project (Project for the Sociolinguistic Study of Spanish in Spain and America), which is representative of spoken language, and a collection of online editorials published by the newspaper El País. The data analysis reveals that aunque can function discursively to mark topical discontinuity, either through rupture or topical splitting. In the latter case, the connective aunque is used both to introduce insertions like parentheses into ongoing discourse.